Targeting peace understanding UN and EU targeted sanctions - Eriksson, Mikael (Routledge Ashgate, 2011)
In recent years, the international community has increasingly abandoned comprehensive sanctions in favour of targeted sanctions. This book argues that this change demands a new way of understanding international sanctions practice. Based on substantial research, this valuable new perspective provides a fresh perspective on targeted sanctions, exploring trends in practice and offering unique case studies for evaluation.